As novas formas de controle em One Dimensional Man, de Herbert Marcuse - Jannarelli, Vicente Claudio (2010)
One-Dimensonal Man deals with certain basic tendencies in contemporary industrial society which seem indicate a new phase of civilization. These tendencies have engendered a mode of thought and behavior which undermined the very foundations of the traditional culture. The main characteristic of this new mode of thought and behavior is the repression of all values, aspirations, and ideas which cannot be defined in terms of operations and attitudes validated by the prevailing forms of rationality. The consequence is the weakening and even the disappearance of all genuinely radical critique, the integration of all opposition in the established system. Herbert Marcuse develops, in One-Dimensional Man, a model both of his critical social theory and of his critical philosophy inspired by his philosophical studies and his work with the Frankfurt School. Also describes a the mechanisms through which the advanced industrial society integrates individuals into its world of thought and behavior. Identifying these mechanisms - the new forms of control , according to Marcuse - their origin, the relationship and synergy amongst themselves are the main scopes of this present job